The effects of the COVID-19 pandemic on training volume, intensity distribution, and racing practices of cyclists - Smith, P.; Taylor, J.; Berger, N. (Journal of Science and Cycling, 2025)
The COVID-19 pandemic of 2020 led governments around the world to respond by imposing lockdown restrictions, which limited the ability of cyclists to train and race as they typically would. While limited research describes the impact on professional and elite riders, less is known about the impact on recreational/sub-elite riders. Given that cyclists of this level contribute a high proportion of the cycling population, we set out to conduct a survey to determine the impact of COVID-19 on their training and racing practices. Questions covered their demographics and background, followed by their typical training, such as regular session type and frequency, training intensity distribution, and their racing practices. A total of 146 cyclists responded, and results revealed that despite decreases in the general population`s physical activity levels, 71.9% of respondents actually increased their cycling volume in 2020, with a significantly higher volume in every month in 2020 compared to 2019. Intensity distribution was also modified due to lockdowns, the volume of high intensity training was increased by 30.7% of respondents, while 37.3% decreased their high intensity training volume, often alongside an increase in overall volume. Racing practices were also altered, in-person racing dropped 56.6%, while e-racing on platforms such as Zwift increased by 114.7%. Despite the challenges, 67.9% of respondents reported feeling fitter in 2020, and 57.8% specifically felt the period of lockdown increased their fitness. These findings highlight the adaptability of recreational and sub-elite cyclists and their resilience to endure an unprecedented global pandemic.